Polysaccharide intercellular adhesin in biofilm: structural and regulatory aspects - Arciola, Carla Renata; Campoccia, Davide; Ravaioli, Stefano; Montanaro, Lucio (Frontiers in Cellular and Infection Microbiology, 2015)
Staphylococcus aureus and Staphylococcus epidermidis are the leading etiologic agents of implant-related infections. Biofilm formation is the main pathogenetic mechanism leading to the chronicity and irreducibility of infections. The extracellular polymeric substances of staphylococcal biofilms are the polysaccharide intercellular adhesin (PIA), extracellular-DNA, proteins, and amyloid fibrils. PIA is a poly-β(1-6)-N-acetylglucosamine (PNAG), partially deacetylated, positively charged, whose synthesis is mediated by the icaADBC locus. DNA sequences homologous to ica locus are present in many coagulase-negative staphylococcal species, among which S. lugdunensis, however, produces a biofilm prevalently consisting of proteins. The product of icaA is an N-acetylglucosaminyltransferase that synthetizes PIA oligomers from UDP-N-acetylglucosamine. The product of icaD gives optimal efficiency to IcaA. The product of icaC is involved in the externalization of the nascent polysaccharide. The product of icaB is an N-deacetylase responsible for the partial deacetylation of PIA. The expression of ica locus is affected by environmental conditions. In S. aureus and S. epidermidis ica-independent alternative mechanisms of biofilm production have been described. S. epidermidis and S. aureus undergo to a phase variation for the biofilm production that has been ascribed, in turn, to the transposition of an insertion sequence in the icaC gene or to the expansion/contraction of a tandem repeat naturally harbored within icaC. A role is played by the quorum sensing system, which negatively regulates biofilm formation, favoring the dispersal phase that disseminates bacteria to new infection sites. Interfering with the QS system is a much debated strategy to combat biofilm-related infections. In the search of vaccines against staphylococcal infections deacetylated PNAG retained on the surface of S. aureus favors opsonophagocytosis and is a potential candidate for immune-protection.